Concurrent Photocatalytic Hydrogen Generation and Dye Degradation Using MIL‐125‐NH2 under Visible Light Irradiation. (5th November 2018) - Kampouri, Stavroula; Nguyen, Tu N.; Spodaryk, Mariana; Palgrave, Robert G.; Züttel, Andreas; Smit, Berend; Stylianou, Kyriakos C.
Abstract: The impact of different transition metal‐based co‐catalysts toward photocatalytic water reduction when they are physically mixed with visible‐light active MIL‐125‐NH2 is first systematically studied. All co‐catalyst/MIL‐125‐NH2 photocatalytic systems are found to be highly stable after photocatalysis, with the NiO/MIL‐125‐NH2 and Ni2 P/MIL‐125‐NH2 systems exhibiting high hydrogen (H2 ) evolution rates of 1084 and 1230 µmol h −1 g −1, respectively. Second, how different electron donors affect the stability and H2 generation rate of the best Ni2 P/MIL‐125‐NH2 system is investigated and it is found that triethylamine fulfils both requirements. Then, the electron donor is replaced with rhodamine B (RhB), a dye that is commonly used as a simulant organic pollutant, with the aim of integrating the photocatalytic H2 generation with the degradation of RhB in a single process. This is of supreme importance as replacing the costly (and toxic) electron donors with hazardous molecules present in wastewater makes it possible to oxidize organic pollutants and produce H2 simultaneously. This is the first study where a metal–organic framework (MOF) system is used for this dual‐photocatalytic activity under visible light illumination and the proof‐of‐concept approach envisions a sustainable waste‐water remediation process driven by the abundant solar energy, while H2 is produced, captured, and further utilized. Abstract : Dual photocatalytic activity : Using a twofold strategy, the impact of different co‐catalysts and electron donors in a metal–organic framework photocatalytic system toward water reduction is investigated. Drawing on these insights, the electron donor is replaced with an organic dye and achieves simultaneous photocatalytic hydrogen production and dye degradation.